Current Strategies for Cancer Cell-Derived Extracellular Vesicles for Cancer Therapy - Gong, Xiaolin (Frontiers in Oncology, 2021)
Cancer cell-derived extracellular vesicles (CEVs), a novel type of therapeutic agent in cancer treatment, can be prepared from the autocrine secretion of various cancer cells, the direct extraction of cancer cells and the combination of cancer cell-derived membranes with advanced materials. With various bioactive molecules, exosomes are produced by cells for intercellular communication. Although cancer cell-derived exosomes are known to inhibit tumor apoptosis and promote the progression of cancer, researchers have developed various innovative strategies to prepare anti-tumor vesicles from cancer cells. With current strategies for anti-tumor vesicles, four different kinds of CEVs are classified including irradiated CEVs, advanced materials combined CEVs, chemotherapeutic drugs loaded CEVs and genetically engineered CEVs. In this way, CEVs can not only be the carriers for anti-tumor drugs to the target tumor area but also act as immune-active agents. Problems raised in the strategies mainly concerned with the preparation, efficacy and application. In this review, we classified and summarized the current strategies for utilizing the anti-tumor potential of CEVs. Additionally, the challenges and the prospects of this novel agent have been discussed.